The Impact of Green Human Recourses Management Practices on Job Performance – The Mediating Role of Resistance to Change: An Applied Study on Jordanian Manufacturing Companies - Al Hashem, Rand O.; Al Shaar, Eshaq M. (Jordan Journal of Business Administration, 2022)
This study aimed at investigating the impact of green human resources management (GHRM) practices on job performance in light of resistance to change as a mediating variable. To achieve the study objectives, the descriptive analytical approach was used. The questionnaire was distributed to (66) companies. Comprehensive survey method was used to distribute the questionnaire to (200) occupants of leadership and supervisory positions in industrial companies that apply (GHRM) practices or have an environmental certification. The results showed that (GHRM) has a positive direct impact on job performance. The study also concluded that resistance to change has a negative impact on job performance. In addition, the study found that (green training and development, green reward and compensation) decrease resistance to change. Moreover, the results showed that resistance to change mediates the impact of (green training and development, green reward and compensation) on job performance; whereas resistance to change does not mediate the impact of (green job design and analysis, green staffing, performance management and appraisal) on job performance. The study recommended to increase employee awareness and knowledge of green practices and environmental sustainability.